CFRP fire behaviour - passive protection system - Ferreira, Débora (2018)
The technique of reinforcing concrete structures by means of bonding composite fibre reinforced polymers (FRP) has been applied in the construction industry. There are several examples of application of these materials in bridges and in buildings, both in new construction and rehabilitation and/or strengthening of damaged structures. With the increasing use of FRP new problems and challenges are inevitably found. Among these subjects, there are legitimate concerns about the behaviour of FRP materials when exposed to fire action. It is the aim of this work to analyse the behaviour of composite materials exposed to fire, in particular composite materials based on carbon fibres (CFRP). Therefore a set of tests on 100 × 100 × 40 mm concrete specimens with CFRP are to be analysed using the test method recommended by EN ISO 13927. The CFRP sheet is glued on the top surface of the specimens using epoxy resin and exposed to thermal action. The surface of the reinforcement system is exposed to the action of different radiative heat fluxes, from 35 kW/m2 to 75 kW/m2, from a cone calorimeter and changes in temperature are determined by thermocouples placed between the surfaces of both materials, and the material heat release rate by the use of a thermopile. The influence of passive fire protection systems on the CFRP fire reaction is analysed considering different fire protection materials (gypsum boards, ceramic fibre sheets and intumescing paints). The temperature variation during the period of thermal exposure is measured across the surface of the different material layers, allowing to assess the influence of these fire protection materials to the CFRP structural reinforcement capabilities at elevated temperatures.